Integrated System In Comprehensive Cancer Treatment - Husain, Dr. Farid W (Indonesian Journal of Cancer, 2009)
Program of Action for CancerTherapy (PACT) o The international Atomic Energy Agency (IAEA)took action to combat cancer in developingcountries by launching a Program of Action forCancer Therapy (PACT) in 2004. o PACTâs mission is to improve cancer survival indeveloping countries by generatingradiotherapy investments into public healthsystems. o PACT will meet its goals by building public-private partnership, mobilizing resources fromnontraditional sources and ensuring theeffective and sustainable transfer of radiationmedicine International organizations, civil society and thedonor community must work together to increasethe resources dedicated to : n cancer prevention, n early detection, n treatment n palliative careÂ Full text: http://www.scribd.com/doc/45477705/Integrated-System-In-Comprehensive-Cancer-Treatment